Winning Presentation in a Day Get it done right, get it done fast
Winning Presentation In A Day provides you with the critical, time-tested tools and information you need to choose your content, create your message, and pull together a well-constructed and effective presentation in record time. The book also includes valuable information on how to create an effective PowerPoint presentation. Whether you?re new to PowerPoint, or are a power user who wants to add ?pizzazz? to your presentations, this book shows you how to quickly and easily create slides to enhance your message and hold your listeners? attention.